Regex Quick Syntax Reference Understanding and Using Regular Expressions - Nagy, Zsolt (Apress, 2018)
This quick guide to regular expressions is a condensed code and syntax reference for an important programming technique. Using JavaScript and Perl 6 code, it demonstrates regex syntax in a well-organized format that can be used as a handy reference. The Regex Quick Syntax Reference features short, focused code examples that show you how to use regular expressions to validate user input, split strings, parse input, and match patterns. Utilizing regular expressions to deal with search/replace and filtering data for backend coding is also covered. You won't find any bloated samples, drawn out history lessons, or witty stories in this book. What you will find is a language reference that is concise and highly accessible. The book is packed with useful information and is a must-have for any programmer. You will: Formulate an expression Work with arbitrary char classes, disjunctions, and operator precedence Execute regular expressions and visualize using finite state machines Deal with modifiers, including greedy and lazy loops Handle substring extraction from regex using Perl 6 capture groups, capture substrings, and reuse substrings .